Pengaruh Labelisasi Halal dan Harga Terhadap Minat Mahasiswa Pada Produk Roma Malkist - Sa'diyah, Mahmudatus; Nisa, Dewi Sholihatun (JIOSE: Journal of Indonesian Sharia Economics, 2024)
This study aims to empirically examine the effect of halal labeling and price on student interest in roma malkist products in students of the Faculty of Economics and Business UNISNU Jepara. This study used a descriptive quantitative approach. The population of this study amounted to 889 students with samples taken as many as 90 students. The sampling technique used uses the purposive sampling method. The data analysis technique uses multiple linear regression through the SPSS 21 program. The results of this study show that halal labeling has a significant effect on students' interest in roma malkist products. Data analysis showed the calculation of a regression coefficient of 0.002 with a significance level of t of 0.05. Price has a significant effect on students' interest in roma malkist snack products. This is indicated by a significance value of 0.000 < 0.05. The value of the coefficient of determination in this study is 52.9% so it can be concluded that halal labeling and price affect interest.